Encapsulation of essential oils in SiO2 microcapsules and release behaviour of volatile compounds. (November 2014) - Sousa, F. L.; Santos, M.; Rocha, S. M.; Trindade, T.
Abstract Natural substances derived from plants such as essential oils (EOs) are used in a variety of applications such as in the release of fragrances or active substances in cosmetics, in food industries to protect sensitive ingredients against oxidative processes and as antimicrobial agents. However, the labile and volatile nature of EOs reduces their activity during application or storage. Here, the microencapsulation of EOs in silica capsules was investigated as a mean to control the fast release of their volatile constituents. The preparation of silica capsules with oil cores was obtained by employing a sol-gel method to oil-in-water-in-oil (O/W/O) multiple emulsions. The volatile release from the SiO2 capsules was investigated by comprehensive two-dimensional gas chromatography with time of flight mass spectrometry detection (GC × GC–ToFMS). This research demonstrates that the SiO2 capsules have selectively encapsulated the different volatile species and the corresponding release profiles depend on the chemical properties of each component.